2003
DOI: 10.1037/0894-4105.17.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Line Bisection in the Split Brain.

Abstract: The authors examined line bisection in 4 patients with resection of the corpus callosum and in 22 control participants. The control participants showed a leftward bias, especially with the left hand, implying right-hemispheric dominance in spatial attention. Two patients with anterior callosotomy showed similar biases, suggesting that the anterior callosum plays only a small role. A patient with complete callosotomy showed a strong right bias, regardless of hand use. A patient with posterior callosotomy showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 40 publications
5
27
0
Order By: Relevance
“…To investigate whether the effect observed in Experiment 1 is specific to emotion lateralization or can be replicated in a lateralized task that is purely cognitive in nature, we conducted Experiment 2. When asked to manually bisect horizontal lines in the center, participants usually deviate towards the left of the veridical center (e.g., Hausmann et al, 2002;2003a;2003b) -a phenomenon called pseudoneglect (Bowers and Heilman, 1980a). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate whether the effect observed in Experiment 1 is specific to emotion lateralization or can be replicated in a lateralized task that is purely cognitive in nature, we conducted Experiment 2. When asked to manually bisect horizontal lines in the center, participants usually deviate towards the left of the veridical center (e.g., Hausmann et al, 2002;2003a;2003b) -a phenomenon called pseudoneglect (Bowers and Heilman, 1980a). …”
Section: Methodsmentioning
confidence: 99%
“…Hausmann et al, 2002;2003a;2003b;Najt et al, 2013). The task was comprised of 17 horizontal, black lines of 1 mm width on a white sheet of A4 paper.…”
Section: Line Bisection (Lb) Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, however, one challenge to the interpretation that the ECFT strongly supports the Right Hemisphere Hypothesis is that the leftward bias is not a phenomenon restricted to emotional chimeric faces but also applies to visuospatial attention. This is demonstrated in numerous tasks, such as line bisection in neurotypical individuals, and has been termed 'pseudoneglect' (Bowers & Heilman, 1980;Hausmann, 2005;Hausmann, Corballis, & Fabri, 2003, Hausmann, Ergun, Yazgan, & Güntürkün, 2002see Jewell & McCourt, 2000, for a review). In much the same way that a left hemiface bias in the ECFT is thought to indicate right hemispheric emotional face processing, the leftward biases shown towards stimuli in pseudoneglect tasks suggest a right hemispheric dominance in the allocation of attention, and as such stimuli in the left visual space are favoured over those in the right visual space (e.g., Hausmann, Corballis, & Fabri, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, another explanation could be found in the literature on split-brain patients. In fact, several studies carried out with split-brain patients showed -only following total resection -a sort of attentional deficit of the right hemisphere [58,59,24]. In the present study, the use of the sole right hand in providing responses, makes it difficult to conclude if D.D.V.…”
Section: Discussionmentioning
confidence: 75%